Functional materials technological aspects of production and processing : special topic volume with invited peer reviewed papers only - Zidani, Mosbah; Miroud, Djamel; Hichem, Farh (Diffusion foundations, 2018)
All parts of this special topic volume have been carefully developed and collected in order to provide the reader with an understanding of the various concepts resulting from research activities accumulated in a wide variety of technological areas of production and processing of functional materials.